Evaluation of the Gelation Characteristics and Printability of Edible Filamentous Fungi Flours and Protein Extracts - Lauren Doyle; Suvro Talukdar; Youling L. Xiong; Akinbode Adedeji; Tyler J. Barzee (Foods)
There is a pressing need to produce novel food ingredients from sustainable sources to support a growing population. Filamentous fungi can be readily cultivated from low-cost agricultural byproducts to produce functional proteins for food biomanufacturing of structured products. However, there is a lack of scientific knowledge on the gelling characteristics of fungal proteins or their potential in additive biomanufacturing. Therefore, this study investigated the feasibility of utilizing fungal protein extracts and flours from Aspergillus awamori, Pleurotus ostreatus, Auricularia auricula-judae as sole gelling agents in 3D-printed products. Protein extracts were successfully prepared using the alkaline extraction–isoelectric precipitation method and successful physical gels were created after heating and cooling. Results indicated that shear-thinning gel materials could be formed with acceptable printability at mass inclusion rates between 15% and 25% with the best performance obtained with P. ostreatus protein extract at 25% inclusion. A. auricula-judae demonstrated promising rheological characteristics but further optimization is needed to create homogeneous products appropriate for extrusion-based 3D printing. This work provides valuable insights for continued development of 3D-printed foods with filamentous fungi.